Psychotic symptoms in Chinese patients with somatic symptom disorder: prevalence, risk factors, and associated conditions - Yuan, Jiamei; Zhong, Yunhui; Li, Yibo; Liao, Yuanping; Tang, Hong (Frontiers in Psychiatry, 2025)
Psychotic symptoms are prevalent in individuals with various mental health disorders and frequently lead to adverse outcomes. In this study, we assessed the prevalence of psychotic symptoms and its associated conditions in a large sample of Chinese patients with somatic symptom disorder (SSD), which has not been examined systemically. We recruited 899 patients with SSD. We used the positive subscale of the Positive and Negative Syndrome Scale to assess psychotic symptoms in the participants. We evaluated the participants using the Hamilton Depression Rating Scale (HAMD), Hamilton Anxiety Rating Scale (HAMA) and Perceived Stress Scale (PSS).The prevalence of psychotic symptoms in participants was 10.2%. Compared with participants without psychotic symptoms, participants with psychotic symptoms had higher scores on the HAMD, HAMA and PSS scales and a shorter sleep duration. Based on the results of stepwise binary logistic regression analysis, the HAMA, HAMD and PSS were significantly associated with psychotic symptoms in the participants. Our findings suggest that psychotic symptoms are common in patients with SSD in the Chinese Han population. In addition, greater levels of anxiety, depression, and stress are potentially useful markers for predicting a greater risk of psychotic symptoms.